HUBUNGAN DERAJAT RETARDASI MENTAL DENGAN KEMAMPUAN AKTIVITAS SEHARI-HARI DI SLB DHARMA WANITA PERSATUAN PROVINSI BENGKULU - Sutri Yani; Nengke Puspita Sari (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
In Indonesia an estimated incidence rate of severe mental retardation approximately 0,3% of the entire population, and almost 3% had an IQ value below 70. As a human resources they can not be used, because 0,1% of these children require care, guidance and supervision throughout his life. Because unknown children level of independence in activities of daily living based on the degree of mental retardation then he study was aimed to know the relationship of the degree of mental retardation and ability of daily living activities. This study used cross sectional design. The population was 37 people with using total sampling, then using secondary and primary data are processed in a univariabel and bivariabel. This study was conducted in 2017 at SLB Bengkulu Province. The results showed that most of the 37,8% has a severe degree of mental retardation, and most of the 51,4% children with mental retardation have an inability to carry out activity of daily living. The results of bivariabel analysis by chi-square test found that p=0,005, a significant relationship between the degree of mental retardation and ability of daily living activities. In addition to special education in school children with mental retardation should also be trained and guided by parents in carry out activities of daily living to be independent and adapt to daily life without assistance. Keywords : ADL, children, degree of mental retardation